2001
DOI: 10.1093/emboj/20.17.5008
|View full text |Cite
|
Sign up to set email alerts
|

Hrs recruits clathrin to early endosomes

Abstract: The hepatocyte growth factor-regulated tyrosine kinase substrate, Hrs, has been implicated in intracellular traf®cking and signal transduction. Hrs contains a phosphatidylinositol 3-phosphate-binding FYVE domain that contributes to its endosomal targeting. Here we show that Hrs and EEA1, a FYVE domain protein involved in endocytic membrane fusion, are localized to different regions of early endosomes. We demonstrate that Hrs co-localizes with clathrin, and that the C-terminus of Hrs contains a functional clath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
348
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(385 citation statements)
references
References 70 publications
34
348
0
3
Order By: Relevance
“…Anti-Cbl (RF) and anti-EGFR (RK2) antibodies were described previously. Affinity-purified rabbit antibodies against recombinant Hrs have been described previously 16 . Mouse monoclonal antibodies against the human transferrin receptor (B3-25) were obtained from Boehringer Mannheim (Mannheim, Germany).…”
Section: Reagents Cells Plasmids and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-Cbl (RF) and anti-EGFR (RK2) antibodies were described previously. Affinity-purified rabbit antibodies against recombinant Hrs have been described previously 16 . Mouse monoclonal antibodies against the human transferrin receptor (B3-25) were obtained from Boehringer Mannheim (Mannheim, Germany).…”
Section: Reagents Cells Plasmids and Antibodiesmentioning
confidence: 99%
“…S4c). The ability of Hrs to bind and recruit clathrin is thought to be important for its function as an endosomal sorting receptor 16 , and we considered the possibility that ubiquitination could affect clathrin recruitment to endosomes. However, overexpression of both Hrs and the Hrs-ubiquitin chimera equally recruited clathrin to early endosomes, whereas Hrs(1-706), which lacks the clathrin-binding C terminus, did not cause any clathrin recruitment (see Supplementary Information, Fig.…”
mentioning
confidence: 99%
“…Five Ala and/or Gly residues (9,16,28,35) are highly conserved and are involved in the formation of an 'Alanine zipper' between the first two helixes (see Supplementary material Figure S4) [64]. The 'Alanine zipper' also participates in the coiled coil formation as a result of its interaction with aromatic and/or large hydrophobic side-chain residues as Leu, Tyr and Ile.…”
Section: Vps4mentioning
confidence: 99%
“…HIV, MuLV and RSV) and in lipid partitioning [7,8]. However, MVBs are also central for sorting vacuolar proteins directly from the late Golgi to the anterograde and biosynthetic pathway ( Figure 1) [9]. Furthermore, MVBs operate in the exocytotic pathway and the secreted interluminal vesicles are known as exosomes (Figure 1) [10][11][12].…”
mentioning
confidence: 99%
“…Based on the work with the dynamin specific GTP hydrolysis inhibitor dynasore, it was recently proposed that dynamin may in fact act at two different stages in clathrin-vesicle formation, (Macia et al, 2006). Using dynasore, the authors observed the arrest of clathrin-coated vesicle formation at two different stages, both Dynamin has been demonstrated to be involved in recycling from early endosomes to the TGN (Nicoziani et al, 2000) and dynamin has also been shown to be recruited to early endosomal clathrin coats upon overexpression of the endosomal sorting-protein Hrs (Raiborg et al, 2001a). Recycling of the TfR has been proposed to follow two distinct pathways, one pathway where dynamin is involved in transport from the early endosome to the recycling endosome, and another pathway different from that via the recycling endosome (van Dam et al, 2002).…”
Section: Dynaminmentioning
confidence: 99%